Sperm DNA fragmentation index, as measured by sperm chromatin dispersion, might not predict assisted reproductive outcome - Tie-Cheng Sun; Yan Zhang; Hong-Tu Li; Xi-Ming Liu; Dong-Xu Yi; Li Tian; Yi-Xun Liu (Elsevier, 2018)
Objective: Routine semen parameters have limited clinical diagnostic value for predicting male infertility. The aim of this study was to investigate the association between sperm DNA fragmentation index (DFI) and semen quality, and between DFI and clinical pregnancy rate of in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI). Methods and materials: A total of 390 couples undergoing sperm fragmentation prior to receiving conventional IVF (n = 238) or ICSI (n = 152) were evaluated. Results: We found that there were no significant differences in fertilization rate, good embryo rate, or pregnancy rate between high (≥30%) and low (<30%) DFI groups after IVF or ICSI. However, statistically different decreasing motility trends under higher DFI values in the IVF and ICSI groups were detected. Comparison of ROC curve of motility and DFI scores for achieved pregnancy revealed that the best DFI cut-off value was 20%. Also, no significant change was found when 20% DFI level was taken in IVF and ICSI outcomes. Conclusion: DFI scores did not provide independent information regarding fertilization, embryo quality, or pregnancy for infertile patients who received IVF or ICSI, but were consistent with semen analysis for infertile couples, regardless of IVF or ICSI outcome. Keywords: Sperm DNA fragmentation (DFI), Sperm motility, IVF/ICSI, Clinical pregnancy rate